Divination processes : an examination of the incorporated belief systems of several Nguni diviners and the subsequent effects on the symbolism, form, structure and style of the music associated with their ritual practices - Stinson, Kathryn Lee (College of Music, 2024)
The traditional musical practices of the Nguni people of Southern Africa are of a social nature, directed at fulfilling specific functions. Divination music in particular is of no exception, and it is intricately linked to the methodology and religious symbolism employed by Southern Nguni diviners, providing proof of the role of the ancestors as protectors of health and welfare of their living descendants. Divination songs are a means of artistic expression and communication between the ancestors and the people, and are performed in the context of rituals in which they convey special meanings and serve a certain purpose. This study is concerned with structures of divination and several methods employed by Nguni diviners (ie. of Zulu, Xhosa and Swazi origin). My analysis of the training of diviners and the examination of particular rituals performed by certain Southern Nguni diviners, is carried out in the context of their world view and systems of beliefs, as documented in current anthropological literature and in the words of my informants. I also attempt to examine innovations arising from cross-culturalisation, which find expression in such ritual action.